Hydrophobic gold nanostructures via electrochemical deposition for sensitive SERS detection of persistent toxic substances1. Issue 18 (5th March 2015) - Jing, Lixiao; Shi, Yu-e; Cui, Jingcheng; Zhang, Xiaoli; Zhan, Jinhua
<x xml:space="preserve">Abstract</x> The hydrophobic gold nanostructures were used for direct SERS detection of PTS with high sensitivity.